The growth of informal sector and urban management challenges. The case of zengeza 4 in chitungwiza - Chasi, Lisa (Midlands State University, 2017)
The purpose of this research was to examine the growth of informal sector and how it has several impacts on urban management in Chitungwiza Zengeza 4 which led to challenges on resources such as water, housing, sewer system and waste management, affecting development according to (the basic needs approach) hence challenges on the deliverance of the local authority and affecting the nation at large. Particular attention is on when and how the informal sector rose in Chitungwiza, the extent at which it has affected the local authority; how the local authority is dealing with the informal sector and the strategies they have put across to curb the problems, the successes and failures. Particular attention has also been given to the extent on the people and type of jobs they do and their participation in the informal sector and the city fathers. Semi-structured questionnaires and interviews were used to collect the information from the selected respondents. The results were based on the information captured in the questionnaires and qualitative face to face interactions. Women tended to participate in culturally defined activities such as selling of both new and second hand clothes, sweets, airtime, sewing bedcovers and sofa covers, fruit and vegetables while men ventured in activities that are more technical such as sofa making, bed making and other kitchen property. Challenges were faced since 1985 but skyrocketed during the 20th century particularly in 2010 after the Operation Murambatsvina which had disturbed the informal sector in 2002. This research pays particular attention to 2010-2014.